Co-Modification of TiNb2O7 with graphene derivatives and Pluronic F127 for enhanced lithium-ion battery anodes - Amirreza Shahbazian; Nafiseh Hassanzadeh (Results in Engineering)
This study focuses on enhancing the performance of TiNb2O7 (TNO) anodes in lithium-ion batteries (LIBs) through a co-modification strategy that combines graphene compositing with morphological control using Pluronic F127. TNO is a promising anode material due to its high theoretical capacity, rapid Li+ intercalation, extended lifecycle, and high safety, but it inherently suffers from low electronic and ionic conductivity. To address this limitation, TNO composites were synthesized using a one-pot solvothermal method with three common graphene derivatives: graphene oxide (GO), reduced graphene oxide (rGO), and electrochemically exfoliated graphene (EEG). Among these, the rGO-based composite demonstrated superior performance due to its balanced conductivity and dispersion properties, achieving an initial discharge capacity of 317 mAh/g at 1C compared to 150 mAh/g for pure TNO. Incorporating Pluronic F127 into the rGO composite further enhanced performance, delivering an initial discharge capacity of 350 mAh/g at 1C and retaining 85 % capacity after 1000 cycles. Additionally, this optimized sample achieved a high discharge capacity of 130 mAh/g at 20C. Electrochemical impedance spectroscopy confirmed reduced charge transfer resistance in the rGO-F127-modified TNO composite, emphasizing the synergistic effects of this dual modification approach. These findings provide a promising pathway for developing high-performance LIB anodes with improved conductivity, stability, and rate capability.